Surface Modification of Nanoclays with Styrene-Maleic Anhydride Copolymers - Uyanık, Nurseli; ARAT, REFİK (Scientific Research, 2017)
This study presents the modification of surfaces of nanoclays, halloysite nanotubes (HNT) and sepiolite (SEP), with styrene-maleic anhydride copolymers (SMA) via esterification reaction between hydroxyl groups of the nanoclays and anhydride groups of SMA. The structural, thermal, and morphological analyses of the modified nanoclays were performed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction analysis (XRD), thermal gravimetric analysis (TGA), and field emission scanning electron microscopy (FESEM). All of these results suggested that the expected modification of HNT and SEP surfaces were performed. Although XRD patterns of HNT containing samples showed that the basal spacing shifted to higher distances, it was found that those of the crystalline structure of SEP remained unchanged. Thermal gravimetric analysis exhibited that SMA copolymers were grafted onto the surfaces of nanoclays varying amounts between 15 and 43 wt. % depending on the types of nanoclays and SMA copolymers. This modification indicates that these nanoclays can be added to the polystyrene matrix without any compatibilizers.
Keywords: Halloysite Nanotubes; Sepiolite; Styrene-Maleic Anhydride Copolymer; Surface Modification of Nanoclays